Flexible Europe differentiated integration, fairness, and democracy - Bellamy, Richard <<[VerfasserIn]>>; Kröger, Sandra <<[VerfasserIn]>>; Lorimer, Marta <<[VerfasserIn]>> (Bristol Bristol University Press, 2022)
The European Union (EU) is often portrayed as sacrificing national diversity for European unity. This book explores the alternative of a flexible EU based on differentiated rather than uniform integration. The authors combine normative theory with empirical research on political party actors to assess the desirability and political acceptability of differentiated integration as a means of accommodating heterogeneity in the EU. They examine the circumstances and institutional design needed for flexibility to promote rather than undermine fairness and democracy within and between member states. Clear, balanced and accessible, the book provides fresh thinking on the future of the EU.
Bibliographie: Seite 168-189